Earnings Manipulation Risk, Corporate Governance Risk, and Auditors' Planning and Pricing Decisions - Bedard, Jean C.; Johnstone, Karla M. (The Accounting Review, 2004)
This paper investigates auditors' assessments of earnings manipulation risk and corporate governance risk, and their planning and pricing decisions in the presence of these identified risks. To conduct this investigation, we use engagement partners' assessments of their existing clients made during the participating public accounting firm's client continuance risk assessment process. We find that auditors plan increased effort and billing rates for clients with earnings manipulation risk, and that the positive relationships between earnings manipulation risk and both effort and billing rates are greater for clients that also have heightened corporate governance risk. These findings provide evidence that auditors assess situations involving both an aggressive management and inadequate corporate governance, and that there is a relationship between those assessments and auditors' planning and pricing decisions.